2022
DOI: 10.1155/2022/4911205
|View full text |Cite
|
Sign up to set email alerts
|

Iron Chelators in Treatment of Iron Overload

Abstract: Patients suffering from iron overload can experience serious complications. In such patients, various organs, such as endocrine glands and liver, can be damaged. Although iron is a crucial element for life, iron overload can be potentially toxic for human cells due to its role in generating free radicals. In the past few decades, there has been a major improvement in the survival of patients who suffer from iron overload due to the application of iron chelation therapy in clinical practice. In clinical use, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 139 publications
(190 reference statements)
0
27
0
Order By: Relevance
“…To investigate the efficacy of iron deprivation in liver cancer treatment, DFO was chosen for further study as it less likely causes rashes, gastrointestinal symptoms, and severe adverse events than DFX does [ 28 ]. We treated 10 hepatic cell lines which consisted of 2 mouse-derived (1 immortalized, 1 malignant) and 8 human-derived (1 immortalized, 7 malignant) liver cell lines (Additional file 1 : Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the efficacy of iron deprivation in liver cancer treatment, DFO was chosen for further study as it less likely causes rashes, gastrointestinal symptoms, and severe adverse events than DFX does [ 28 ]. We treated 10 hepatic cell lines which consisted of 2 mouse-derived (1 immortalized, 1 malignant) and 8 human-derived (1 immortalized, 7 malignant) liver cell lines (Additional file 1 : Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…According to the molecular milieu of endometriotic cysts, a higher level of free iron was reported in both cyst wall and cyst fluid for a long time ( 86 ). Unlike combined iron which plays an essential role in several physiological activities, free iron mediates the generation of reactive oxygen species (ROS) and produces oxygen-free radicals through the Fenton reaction ( 87 ). The surrounding ovarian cortex is affected by excessive oxidative stress and presented a significantly increased expression level of 8-OHdG, a DNA damage marker, compared with benign ovarian cysts ( 88 ).…”
Section: The Mechanisms Of Oma Per Se Leading To O...mentioning
confidence: 99%
“…First, iron chelators can bind to iron in the body to effectively increase iron excretion, thus blocking the redox reaction caused by iron overload. Currently, the main iron chelators used in clinical practice are deferoxamine, 9 Oxidative Medicine and Cellular Longevity deferiprone, and deferasirox [117]. Several studies have shown that iron chelators have cardiovascular protective effects, such as improving vascular endothelial function, inhibiting SMC proliferation, and protecting CMs [64,118].…”
Section: Ferroptosis As a Novel Therapeuticmentioning
confidence: 99%